An Assessment of Gasification of Lipid-Extracted Algae by Thermodynamic Simulation (Journal of Chemical Engineering, 2017)
Thermodynamic simulation of gasification of Nannochloropsis gaditana (after lipid extraction and before lipid extraction) over a wide range of temperatures (800 – 1400 oC) was performed in this study. The reactor temperature variation with respect to the O2 to fuel ratio and the syngas composition with temperature were evaluated for gasification performance. The results showed the H2/CO ratio for lipid-extracted algae (LEA) was very similar to the gasification behavior of raw algae (RA) before lipid extraction. Only a slight variation was observed for the lower heating value (9.2 MJ/Nm3 for RA and 8.9 MJ/Nm3 for LEA at 1000 oC) of the syngas from the two feedstocks. The H2/CO ratio for both RA and LEA remained almost the same over the range of temperatures (800-1400 oC) under consideration. The cold gas efficiency was found between 82 % to 75 % for RA and 75 % to 69 % for LEA at 1000 oC and 1400 oC respectively. As the overall gasification performance did not degrade significantly after extraction of lipid from algae, the LEA holds remarkable potential as a gasification feedstock in a biorefinery set up.Journal of Chemical Engineering, Vol. 30, No. 1, 2017: 59-63